Valuation implications of FAS 159 reported gains and losses from fair value accounting for liabilities - CHUNG, Sung Gon (Institutional Knowledge at Singapore Management University, 2017)
This study examines the economic implications of fair value liability gains and losses arising from the adoption of Statement of Financial Accounting Standards No. 159 (hereafter, FAS 159). Consistent with the notion that gains and losses contain value-relevant information, we find a positive correspondence between a firm’s FAS 159 fair value liability gains and losses and current period stock returns. However, further analysis indicates that fair value gains and losses from liabilities have a negative association with future returns, suggesting that investors misprice this earnings component. This negative association is stronger for firms with low levels of institutional ownership. While the value-relevance tests provide some evidence that fair value changes from liabilities have information content, the negative association with future stock returns suggests that these gains are eventually not realizable or that the market has overreacted to the initial recognition of these gains. Overall, our study contributes evidence regarding the controversy over the recognition of fair value liability gains and losses by providing direct empirical evidence that such gains and losses are priced by the stock market but subsequently reversed within the next 12 months.